DiSVAC the digital signature verification, authentication and certification system - Irigo, Zara A.; Quinton, Suzette C.; Soncuya, Desiree P. (2002)
DiSVAC, or Digital Signature Verification, Authentication and Certification, is an automated web-based system that verifies, authenticates and certifies digital signatures on electronically mailed documents. This could provide and enhance security technology where there is lacking. The main functionality of the system is to verify digital signatures. Thus, it guarantees that messages indeed came from the source or sources the messages appear to have come from. In order to authenticate a digital signature and verify the integrity of the singed message, the sender's Public Key is required. Using the Public Key, the digital signature attached to the message is decrypted. The system will determine if the message has not been altered and if it actually came from the authentic source. The system generates two types of keys, i.e. the private and public keys. Upon registry of a user, he will be prompted to provide some information and an optional "pass phrase." With the application of the RSA algorithm, as set of keys will be generated, and the user will be given his private key for use to generate digital signatures. During encryption of an email message, the message to be signed is hashed with the user's private key that produces the digital signature. This is attached to the message itself when sent through the Internet. The generated public key is stored in the database and can be made available to everybody. Users who want to authenticate documents as coming from a certain source may send a query pertaining to the certain document and encrypted digital signature for verification. The system will send out digital certificates to certify matching signature. The system is implemented using mainly Java technologies and HTML for the web implementation of the system. The system will only cater to digital signature attached to electronically mailed messages (email) although the digital signature although the technology can also be applied to any kind of electronic files and programs.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Digital signatures; Cryptography; DiSVAC (Digital Signature Verification, Authentication and Certification).